THE KNOWLEDGE AND ATTITUDES OF THE COMMUNITY IN SIBANGKAJA VILLAGE, BADUNG, REGARDING THE RABIES INCIDENT: Pengetahuan dan Sikap Masyarakat Desa Sibangkaja, Badung terkait Kejadian Rabies - I Made Subrata; Putu Erma Pradnyani; Sang Gede Purnama; Ni Wayan Arya Utami; Janice Girardi; Kadek Karang Agustina; Ida Bagus Ngurah Swacita; Hendra Irawan; Kate Druhan (Universitas Airlangga, 2023)
Background: The challenges in overcoming the rabies epidemic include the public's lack of knowledge and attitudes regarding the control and first aid in dog bites. Sibangkaja is one of the villages in Badung Regency, which is an endemic area for rabies. Purpose: This study aimed to describe the knowledge, attitudes, and factors influencing the behavior of the residents of Sibangkaja Village, Badung, regarding rabies. Methods: This descriptive observational study was carried out using a cross-sectional design. The samples were 250 residents of Sibangkaja Village, taken by convenience sampling. Data were collected from February to March 2020 through interviews using the digital questionnaire. The variables were knowledge and community attitudes toward rabies vaccination in the village. Results: The results showed that the respondents' knowledge was good, but 34% did not know the symptoms of rabies. It was discovered that attitudes toward rabies prevention and management are significantly more in favor of vaccination than eliminating dogs. Furthermore, there is an association between knowledge and dog ownership on people's attitudes (p-value=0.01). Conclusion: Information and education about the symptoms of rabies is needed for residents to exercise caution and pay more attention to themselves and the surrounding dogs.